2019
DOI: 10.2147/cia.s192586
|View full text |Cite
|
Sign up to set email alerts
|

<p>Carotid artery calcification score and its association with cognitive impairment</p>

Abstract: PurposeTo retrospectively investigate the possible association between carotid artery calcification score (CS) and cognitive impairment in carotid artery stenosis (CAS) patients.Patients and methodsCarotid artery was measured in 102 patients with cervical carotid arteries using Color Doppler ultrasound, multi-detector row spiral CT angiography and MRI scanning. Correlation analysis between CSs obtained by MD CT and cognitive scores was performed, and the correlation between CSs and vascular stenosis degree and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…On the background of a linear relationship between plaque stability and echogenicity, we observed that a minority of patients treated with standard therapy showed a reduction in plaque echogenicity. This finding correlates with the ambiguous role of vascular calcification, that may represent an element of vulnerability in only a minority of patients [ 9 , 10 , 11 , 12 , 26 , 38 ]. In patients with abnormal upregulated calcification, a tailored targeted molecular therapy oriented toward the calcification process, such as vitamin K2 supplementation, may be effective.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…On the background of a linear relationship between plaque stability and echogenicity, we observed that a minority of patients treated with standard therapy showed a reduction in plaque echogenicity. This finding correlates with the ambiguous role of vascular calcification, that may represent an element of vulnerability in only a minority of patients [ 9 , 10 , 11 , 12 , 26 , 38 ]. In patients with abnormal upregulated calcification, a tailored targeted molecular therapy oriented toward the calcification process, such as vitamin K2 supplementation, may be effective.…”
Section: Discussionmentioning
confidence: 65%
“…A recent meta-analysis on the effect of statin therapy on the plaque composition showed a positive increase in the plaque echogenicity up to 35% in 12 months, even if the role of calcium content is not completely understood and still controversial [ 8 ]. Some authors state that it is a stabilizing factor, whereas others consider it a predictor of plaque vulnerability, as it has been recently associated to the presence of cerebral ischemic lesions and cognitive impairment [ 9 , 10 ]. Vitamin K2 (menaquinones) acts as cofactor in the post-translational modification of the gamma-glutamyl carboxylation of glutamate residues in matrix Gla-protein, enhancing its inhibitor role on vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of three factors -stenosis, ulceration of the atherosclerotic plaque and the in ammatory process within it -is one of the leading mechanisms of embologenicity as well as the development of stroke [21,22]. This mechanism is not taken into consideration by the classical approach to determining the indications for carotid endarterectomy where the main criterion is the degree of ICA stenosis (50% in symptomatic patients and 70% in asymptomatic patients).…”
Section: Discussionmentioning
confidence: 99%
“…В научной литературе обсуждается вопрос о том, что ускоренное старение КС связано с их кальцификацией, что непосредственно влияет на высшие психические функции человека. Так, например, кальцификация сонной артерии имеет значительную корреляцию с когнитивными нарушениями, а внутричерепная кальцификация сосудов связана с обширными изменениями белого вещества головного мозга и является причиной выраженных психоневрологических симптомов [23][24][25]. Тем не менее, имеются данные о том, что биологический возраст артерий (жесткость и эластичность) взаимосвязан с факторами риска атеротромбоза.…”
Section: дезадаптивное повреждение сосудистой стенки при старенииunclassified